Code of conduct: using propensity scores to evaluate prison misconduct among veterans in prison - Gloyd, Elizabeth L. (Deviant behavior, 2025)
Over 16 million veterans live in the U.S. but unfortunately, military service is often associated with problematic readjustments back to civilian life, including contact with the criminal justice system. While research has explored the criminal behavior of veterans, less research has focused on the conduct of veterans once they are incarcerated. The current study uses official data from the Florida Department of Corrections to investigate the relationship between veteran status and institutional misconduct. A prisoner release cohort of over 175,000 inmates released from Florida prisons from 2004 to 2011 was used to create more than 8,000 matched pairs of veterans and nonveterans using propensity score matching. After matching, logistic regression and negative binomial regression are used to estimate the association between military service and disciplinary infractions. Results indicate that veterans are less likely to receive a disciplinary infraction for any type of prison misconduct, violent misconduct, and disorderly misconduct compared to nonveterans. Veterans also receive lower numbers of disciplinary infractions as well. The results of this study indicate that the correctional system should address the needs of veterans to aid in their positive reintegration back into society after their service.